2022
DOI: 10.7717/peerj.14506
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a ferroptosis-related lncRNA signature to robustly predict the prognosis, immune microenvironment, and immunotherapy efficiency in patients with clear cell renal cell carcinoma

Abstract: Background Ferroptosis is a new type of iron- and reactive oxygen species-dependent cell death, studies on ferroptosis-related long noncoding RNAs (FerLncRNAs) in clear cell renal cell carcinoma (ccRCC) are limited. The purpose of this study was to investigate the potential prognostic value of FerLncRNAs and their relationship with the immune microenvironment and immunotherapy response of ccRCC. Methods RNA sequencing data of 526 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…There may be two possible factors contributing to lncRNA expression differences. Firstly, inflammation may change lncRNAs expression in the skin lesions, which is supported by the present study, in which immune-related lncRNAs (ENST00000538665, named IFNG-AS1, ENST00000422459, named PELATON) [23,24] were also aberrantly expressed in AI patients. Secondly, other lncRNAs may be induced by defective expression of NCSTN.…”
Section: Discussionsupporting
confidence: 72%
“…There may be two possible factors contributing to lncRNA expression differences. Firstly, inflammation may change lncRNAs expression in the skin lesions, which is supported by the present study, in which immune-related lncRNAs (ENST00000538665, named IFNG-AS1, ENST00000422459, named PELATON) [23,24] were also aberrantly expressed in AI patients. Secondly, other lncRNAs may be induced by defective expression of NCSTN.…”
Section: Discussionsupporting
confidence: 72%
“…Further investigation into these lncRNAs, particularly their roles in ferroptosis, could give new understanding that shed light on the molecular basis of ccRCC. [ 31 ] The prognostic effect of AP006545.1, AC105429.1, and LINC02348 on cancer is little understood. Therefore, more studies are required to analyze how FALs may affect the prognosis of ccRCC caused by ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation into these lncRNAs, particularly their roles in ferroptosis, could give new understanding that shed light on the molecular basis of ccRCC. [31] The prognostic effect of…”
Section: Discussionmentioning
confidence: 99%
“…Several regulatory axes of lncRNAs have been identified that control the invasion and metastasis of ccRCC, such as CDKN2B-AS1/miR-141/CCND1 [29] and RP11-436H11.5/miR-335-5p/BCL-W [30]. Researchers have also investigated ferroptosis-related lncRNAs in ccRCC to identify new biomarkers and establish prognostic models [31]- [32] ,…”
Section: Discussionmentioning
confidence: 99%